Malus domestica: A Review on Nutritional Features, Chemical Composition, Traditional and Medicinal Value - Patocka, Jiri; Bhardwaj, Kanchan; Klimova, Blanka; Nepovimova, Eugenie; Wu, Qinghua; Landi, Marco; Kuca, Kamil; Valis, Martin; Wu, Wenda (Plants (Basel, Switzerland), 2020)
Fruit-derived bioactive substances have been spotlighted as a regulator against various diseases due to their fewer side effects compared to chemical drugs. Among the most frequently consumed fruits, apple is a rich source of nutritional molecules and contains high levels of bioactive compounds. The main structural classes of apple constituents include polyphenols, polysaccharides (pectin), phytosterols, and pentacyclic triterpenes. Also, vitamins and trace elements complete the nutritional features of apple fruit. There is now considerable scientific evidence that these bioactive substances present in apple and peel have the potential to improve human health, for example contributing to preventing cardiovascular disease, diabetes, inflammation, and cancer. This review will focus on the current knowledge of bioactive substances in apple and their medicinal value for human health.
Keywords: human health; polysaccharide; apple; bioactive compounds; polyphenol; phytosterol; triterpene